Complications of Acute Rhinosinusitis in the pediatric population - 10 years at Hospital Garcia de Orta - Areias, Catarina (2021)
Objectives: Complications of acute rhinosinusitis (ARS) carry a potential risk of severe morbility and fatal outcome, and are more frequent in the pediatric population. The authors aim to describe complications of ARS in need of hospitalization: clinical features, epidemiology and medical and surgical treatment in our institution. Study design: Observational retrospective. Material and methods: Assessment of medical files of pediatric patients who were admitted to the Pediatric Emergency Room and later hospitalization, over a 10-year period (2010-2019). Results: Forty-six children were included in this study. There were 43 orbitary complications (93,5%) reported, 3 intracranial complications (6,5%) and 1 bony complication associated with a intracranial complication. Eight children with orbital complications were submitted to surgery. All intracranial complications were operated. Conclusion: There was a good response to high doses of intravenous antibiotics in orbital complications. A multidisciplinary approach must be conducted in order to achieve an optimal treatment.